Problem-Elephant Translocation: Translocating the Problem and the Elephant? - Fernando, Prithiviraj; Leimgruber, Peter; Prasad, Tharaka; Pastorini, Jennifer (PLOS ONE, 2012)
Human-elephant conflict (HEC) threatens the survival of endangered Asian elephants (Elephas maximus). Translocating “problem-elephants” is an important HEC mitigation and elephant conservation strategy across elephant range, with hundreds translocated annually. In the first comprehensive assessment of elephant translocation, we monitored 16 translocations in Sri Lanka with GPS collars. All translocated elephants were released into national parks. Two were killed within the parks where they were released, while all the others left those parks. Translocated elephants showed variable responses: “homers” returned to the capture site, “wanderers” ranged widely, and “settlers” established home ranges in new areas soon after release. Translocation caused wider propagation and intensification of HEC, and increased elephant mortality. We conclude that translocation defeats both HEC mitigation and elephant conservation goals.